2016
DOI: 10.1016/j.resp.2016.09.002
|View full text |Cite
|
Sign up to set email alerts
|

The effects of curvature and constriction on airflow and energy loss in pathological tracheas

Abstract: This paper considers factors that play a significant role in determining inspiratory pressure and energy losses in the human trachea. Previous characterisations of pathological geometry changes have focussed on relating airway constriction and subsequent pressure loss, however many pathologies that affect the trachea cause deviation, increased curvature, constriction or a combination of these. This study investigates the effects of these measures on tracheal flow mechanics, using the compressive goitre (a thyr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
25
0
1

Year Published

2017
2017
2020
2020

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 44 publications
(27 citation statements)
references
References 39 publications
1
25
0
1
Order By: Relevance
“…Analysis of the motion of the jaw, tongue, pharyngeal walls, soft palate, and epiglottis revealed how each region of anatomy influences the volume of the airspace and the cross‐sectional area of the upper airway along its length. Many studies have previously shown the relationship between airway cross‐sectional area and airway resistance, with narrower sections increasing the subject's work of breathing. Therefore, mapping the dynamic behavior of the upper airway cross‐section throughout a breath is vital to accurately predicting the airway pressure losses in computational and experimental models.…”
Section: Discussionmentioning
confidence: 99%
“…Analysis of the motion of the jaw, tongue, pharyngeal walls, soft palate, and epiglottis revealed how each region of anatomy influences the volume of the airspace and the cross‐sectional area of the upper airway along its length. Many studies have previously shown the relationship between airway cross‐sectional area and airway resistance, with narrower sections increasing the subject's work of breathing. Therefore, mapping the dynamic behavior of the upper airway cross‐section throughout a breath is vital to accurately predicting the airway pressure losses in computational and experimental models.…”
Section: Discussionmentioning
confidence: 99%
“…In order to investigate these possibilities in each patient, the internal pressure forces that act on the tracheal walls and the effect that tracheal motion has on subjects' breathing effort can be calculated through computational fluid dynamics (CFD) simulations. Previously, CFD simulations have been used to calculate the increased tracheal work of breathing in adult subjects with goiters and a transplanted trachea . These simulations rely on high‐resolution imaging to provide the anatomical boundaries of the airway structure, and there is increasing recognition that the accuracy of CFD simulations suffers when airway wall motion is ignored and simplified into a static model …”
Section: Discussionmentioning
confidence: 99%
“…Analysis of convergence data was performed on one geometry (case B in Bates et al [1] and shown in Fig. 1).…”
Section: Experimental Design Materials and Methodsmentioning
confidence: 99%
“…As an example of typical averaging windows, in Bates et al [1] all computations were simulated for 0.25 s of steady inhalation. Of this period, the first 0.1 s was ignored, to allow for transients caused by the impulsive start to die away.…”
Section: Experimental Design Materials and Methodsmentioning
confidence: 99%